Morpho-anatomical aspects of Paepalanthus hilairei Koern (Eriocaulaceae) from Serra do Cipo MG - Scatena, V. L.; Barros, ADE (Inst Tecnologia Parana, 1996)
The morphological characteristics of seedlings and the anatomical characteristics of vegetative organs and floral scape of P. hilairei (Eriocaulaceae) were analyzed to investigate the ecological and taxonomic implications for the species. P. hilairei is a perennial plant with an aerial stem and it grows in recently decomposed stony, sandy soils of the Serra do Cipo, in the State of Minas Gerais, Brazil. It is found both on wet and dry soils, exposed to constant winds, high light intensities and extreme daily fluctuations of temperature. The results show that the seeds have operculum and the initial seedling development stages are the same for other Eriocaulaceae. During the germination period, the undifferentiated axis of the embryo becomes apparent. The observation of the development of this axis, shows first, the growth of the leaves and later that of the adventitious root. Attention is focused on the apical stem region which presents sterelis lateral branching with adventitious roots in its base which will develop into paraclades (system of florescences). Both of them rise out of the pericycle and characterize its vegetative growth. The occurrence of a special leaf substomatal chamber may be related to an efficient protection for the gaseous exchange and may be considered an important characteristic of the Eriocaulaceae.
Keywords: morphological and anatomical aspects; Paepalanthus hilairei; Eriocaulaceae; seedling